Barriers to self-management engagement among community-dwelling older adults with mild cognitive impairment: a qualitative study - Jingxian Sun; Yayi Zhao; Aihong Wang (Frontiers in Psychiatry)
IntroductionSelf-management is crucial for individuals with mild cognitive impairment (MCI) to enhance cognitive health and mitigate the potential risk of dementia. However, maintaining consistent engagement in self-management strategies seems a challenge for older adults with MCI. This study sought to gain insights into the barriers to self-management engagement among community-dwelling older adults with MCI.MethodsThis qualitative study used a phenomenological approach. Purposive sampling was used to recruit a diverse group of participants with MCI, aged 60 and above, residing in the provinces of Hubei, Jiangsu, Henan, and Anhui in China. Semi-structured interviews were conducted between January and May 2023, allowing for an in-depth exploration of participants’ experiences and perceptions. The interviews were audio-recorded, transcribed verbatim, and subjected to thematic analysis to capture the essence of the participants’ narratives.ResultsTwenty-six participants participated in the formal semi-structured interviews. The following themes and subthemes were identified: “inappropriate perceptions of MCI” (“low perception of risk from MCI” and “supposition of little personal control over MCI”), “elder self-neglect”, and “lack of available information or support services about MCI”.DiscussionThis study highlights significant barriers to self-management engagement among community-dwelling older adults with MCI, emphasizing the importance of developing tailored interventions that address misconceptions and self-neglect and enhance the availability of information and support services. These findings suggest avenues for policymakers and healthcare providers to foster more effective self-management practices in this population, promoting cognitive health and slowing potential progression to dementia.